2006
DOI: 10.1007/s10517-006-0128-x
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis and proliferative activity in endometrium during peritoneal endometriosis

Abstract: Apoptosis and proliferative activity of the glandular epithelium and endometrial stroma in patients with peritoneal endometriosis and in women of reproductive age without endometriosis were studied at various stages of menstrual cycle. Differences in the intensity of apoptosis were revealed manifesting in changed expression of proteins in the glandular epithelium of patients with endometriosis during the secretory phase of the menstrual cycle compared to normal. Proliferative activity of the glandular epitheli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 8 publications
0
2
0
1
Order By: Relevance
“…For instance, many changes have been found in both the ultrastructral morphology and the molecular composition of the endometrium in patients with endometriosis, providing the basis for a uterine factor in infertility (15)(16)(17). Likewise, polycystic ovary syndrome has also been characterized with specific alterations in the endometrium, including a change in the ratio of estrogen and androgen receptors (18,19).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, many changes have been found in both the ultrastructral morphology and the molecular composition of the endometrium in patients with endometriosis, providing the basis for a uterine factor in infertility (15)(16)(17). Likewise, polycystic ovary syndrome has also been characterized with specific alterations in the endometrium, including a change in the ratio of estrogen and androgen receptors (18,19).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, in our study, the apoptosis rate of the ect-MSCs was not determined along with the inhibition of NOD1 expression. Liu et al (24) found that ect-MSCs exhibited a higher level of proliferation, while Burlev et al (25) observed no difference in the proliferation abilities between ect-MSCs and eut-MSCs. Overall, our study uncovered that the NOD1 li-gand Tri-DAP can promote the proliferation of eut-MSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Many researchers have demonstrated that the eutopic endometrial cell is the essential factor for endometriosis development. 33,34 We used hESCs from patients with endometriosis to evaluate the effect of TNF-α and TNF-α inhibitors on the pathogenesis of endometriosis. Our results showed that TNF-α (0-10 ng/mL) stimulated hESC proliferation in a dose-responsive manner; 1 ng/mL TNF-α significantly promoted the hESC survival rate and S-phase percentage.…”
Section: Discussionmentioning
confidence: 99%